The Effect of Work Stress, Work Competence and Work Motivation on the Performance of Employees of PT. Lancarjaya Mandiri Abadi (Kediri Branch Office) - Afiatujana, Latifa Qori; Bhirawa, Sigit Wisnu Setya (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : The aim of the investigation was to determine whether employees performance at PT. Lancarjaya Mandiri Abadi (Kediri Branch Office) is simultaneously or partially correlated with job competence, work stress, and work motivation. Design/Method/Approach : The current investigation employs a causal research design and a quantitative methodology. Employees of PT. Lancarjaya Mandiri Abadi (Kediri Branch Office) made up the study's population. In order to gather 30 participants from 60 current populations, the sampling technique employs purposive sampling, which involves selecting samples according to specific criteria. Descriptive statistical data analysis approaches, multiple linear regression, coefficient of determination, traditional assumption tests, and SPSSv27 hypothesis testing are all used in this work.. Research Finding : The results showed that variables (1) work stress, work motivation, and work competence had a simultaneous effect on employees performance, (2) work stress, work competence and work motivation had a positively effect on employees performance at PT. Lancarjaya Mandiri Abadi (Kediri  Branch Office). Research limitation : This research has a small scope limitation because it only uses PT. Lancarjaya Mandiri Abadi (Kediri  Branch Office) as a sample of research objects so that it can beused as a research object.